2003
DOI: 10.1038/sj.onc.1207358
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation by the estrogen receptor of antioxidative stress enzymes and its functional implications

Abstract: We previously reported that antiestrogen-liganded estrogen receptor b (ERb) transcriptionally activates the major detoxifying enzyme quinone reductase (QR) (NAD(P)H:-quinone oxidoreductase). Our studies also indicate that upregulation of QR, either by overexpression or induction by tamoxifen, can protect breast cells against oxidative DNA damage caused by estrogen metabolites. We now report on the upregulation of glutathione S-transferases Pi (GST-Pi) and gamma-glutamylcysteine synthetase heavy subunit (GCSh) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 43 publications
(48 reference statements)
4
53
0
Order By: Relevance
“…Estrogens, such as 17beta-estradiol (E2), play an important role in development, growth, and differentiation, and appear to have protective effects on oxidative stress mediated by ER 31) . Inhibitory effects of E2 on atherosclerosis are mediated by COX-2-derived prostacyclin 32) and E2 induces the production of antioxidative enzymes, such as superoxide dismutase 33) , and GST 34) . The effects of E2 are mediated mostly through ER , which functions as a ligandinduced transcription factor and belongs to the nuclear receptor superfamily.…”
Section: Estradiol and Vascular Functionmentioning
confidence: 99%
“…Estrogens, such as 17beta-estradiol (E2), play an important role in development, growth, and differentiation, and appear to have protective effects on oxidative stress mediated by ER 31) . Inhibitory effects of E2 on atherosclerosis are mediated by COX-2-derived prostacyclin 32) and E2 induces the production of antioxidative enzymes, such as superoxide dismutase 33) , and GST 34) . The effects of E2 are mediated mostly through ER , which functions as a ligandinduced transcription factor and belongs to the nuclear receptor superfamily.…”
Section: Estradiol and Vascular Functionmentioning
confidence: 99%
“…Therefore, even relatively modest inductions of phase 2 enzymatic activity can be sufficient to protect against carcinogenesis. Moreover, the ER regulates the expression of other antioxidative enzymes, such as GST-Pi and g-glutamylcysteine synthetase heavy subunit (Montano et al, 2004) in addition to QR, suggesting that ER may play a broad role in protection against antioxidative stress. Finally, breast cancer develops over decades, raising the possibility that chronic, low-level phase 2 enzyme induction might be sufficient to prevent the disease.…”
Section: Controlmentioning
confidence: 99%
“…Possible implication of ER into regulation of GSTP1 expression was demonstrated for the first time in 1988 by Moscow et al who described the negative correlation between ER content and GSTP1 expression in breast cancer cells (Moscow et al, 1988). Later Montano et al demonstrated that ER acts as a positive regulator of GSTP1 expression in the same cells (Montano et al, 2004). Here we found that ER indirectly interacts with two distinct sites of GSTP1 promoter -positive regulatory element ARE and a negative regulatory element CRE and in both cases different transcription factors mediate the effect of ER .…”
Section: Discussionmentioning
confidence: 98%
“…The diversity includes transcription factor AP-1 in breast cancer cells VCREMS (Moffat et al, 1994) and in leukemia cells K562 (Duvoix et al, 2004a); transcription factor NF-E2 in K562 cells (Borde-Chiche et al, 2001); RAR in HeLa cells (Xia et al, 1996) and ER in complex with Jun/Fos or with Nuclear Factor E2 related factor (Nrf2) in mammary carcinoma cells MDA-MB-231 (Montano et al, 2004). It is interesting that transcription factors Jun and Fos in the latter complex cannot activate GSTP1 transcription themselves but they recruit ER and the whole complex substantially activates transcription and mediates up-regulation of GSTP1 expression by estradiol and antiestrogen tamoxifen (Montano et al, 2004). It is also noteworthy that in Me45 cells ER indirectly interacts not only with antioxidant response element ARE, but also with cAMP response element CRE in complex with transcription factor Fos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation